IDENTIFIKASI SENYAWA YANG BERPOTENSI SEBAGAI ANTIDIABETES PADA EKSTRAK ETANOL 30% DAUN KUMIS KUCING (Orthosiphon aristatus) HASIL KULTUR JARINGAN DAN BUDIDAYA - Farhan; Syamsudin; Fahrauk Farayamuda; Nancy Dewi Yuliana (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2026)
Orthosiphon aristatus ( cat's whiskers ) is traditional medicinal plant that contains many secondary metabolite compound such as flavonoids, phenolics acids, and diterpene derivatives and can be used to treat metabolic disorder including inflammation , urinary tract disorders and diabetes. This study aims to compare the secondary metabolite profile of 30% ethanol extract of cat's whiskers leaves from tissue culture and conventional cultivation. Extraction was carried out using Ultrasonic Assisted Extraction (UAE) method and the compounds were identified using Liquid Chromatography–High Resolution Mass Spectrometry (LC-HRMS). The analysis results showed that there were 5 types of dominant compounds in the tissue culture extract, including rosmarinic acid (20.46%), malic acid (6.34%), quinic acid (5.52%), chicoric acid (4.52%), and vanillylmandelic acid (3.4%). The cultivated extract contained rosmarinic acid (11.36%), malic acid (4.7%), ferulic acid (9.46%), vanillylmandelic acid (4.95%), and methylmalonic acid (4.15%). The compounds epigallocatechin gallate (EGCG), isoquercetin, quercitrin, and carmine were only detected in tissue culture. These results indicate that tissue culture techniques can influence the biosynthesis and accumulation of certain secondary metabolites in plants, thus potentially being used to produce high-quality raw materials in the development of phytopharmaka products.